К вопросу о выявляемости хеликобактерной инфекции у больных с сочетанной патологией - хроническим бронхитом и хроническим пиелонефритом - Макарова, Г.В.; Авраменко, А.А. (Актуальні проблеми транспортної медицини, 2006)
Було комплексно обстежено 45 хворих зі сукупною патологією - хронічним бронхітом та хронічним пієлонефрітом - на наявність гелікобактерної інфекції. В 100% випадків гелікобактерна інфекція була виявлена при високій концентрації - (+++). On importance of the presence of helicobacter infection in the patients suffering from the chronic bronchitis and chronic pyelonephritis
Makarova G. V., Avramenko A.A.
45 patients suffering from the chronic bronchitis and chronic pyelonephritis underwent an all-round examination on the presence of helicobacter infection. The helicobacter infection has been revealed in 100% cases with high concentration - (+++).